Psycholinguistic Aspects of the Semantic Field of the Concept “War” in Modern Media Space - Yuliya Krylova-Grek (Психолінгвістика)
This paper presents modern trends in the change of the semantic field of the concept “war”. Based on the analysis of mass media in Russia, Ukraine and the USA, we demonstrated the regularities and interdependences of the mass media content and changes in the conceptual worldview of the people that consume information. We underlined the link between the changes in the forms of international conflicts and the increase of the units contributing to the semantic field of the concept “war”. We analised how the information and communicative space effects the change of the conceptual (mental, cognitive) worldview of the public.